A Qualitative Study On Barriers And Facilitators And Strategies To Improve Adherence To Antidepressants Among Outpatients With Major Depressive Disorder - Ho, Siew Ching (2017)
Major depressive disorder (MDD) is associated with a high rate of relapse and recurrence. One of the major challenges in treating MDD is patients’ nonadherence to medication. The objectives aimed: (1) to explore the barriers and facilitators of patients’ adherence to antidepressants among outpatients with MDD; (2) to identify strategies that aimed to improve adherence from the perspective of various stakeholders. A qualitative study using semi-structured and individual indepth interviews was conducted in phase I of the study. Thirty participants were purposively sampled from different ethnicities to achieve maximum variation in sampling, and data were collected until it reached thematic saturation.